2014
DOI: 10.1105/tpc.114.126011
|View full text |Cite
|
Sign up to set email alerts
|

Pollen-Specific Activation of Arabidopsis Retrogenes Is Associated with Global Transcriptional Reprogramming  

Abstract: Duplications allow for gene functional diversification and accelerate genome evolution. Occasionally, the transposon amplification machinery reverse transcribes the mRNA of a gene, integrates it into the genome, and forms an RNA-duplicated copy: the retrogene. Although retrogenes have been found in plants, their biology and evolution are poorly understood. Here, we identified 251 (216 novel) retrogenes in Arabidopsis thaliana, corresponding to 1% of protein-coding genes. Arabidopsis retrogenes are derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 60 publications
4
36
0
Order By: Relevance
“…TE movements bring sequence changes to open chromatin regions, which may also aid the birth of de novo genes. Abdelsamad and Pecinka (2014) reported pollen-specific activation of 216 novel retrogenes in Arabidopsis, which supports the hypothesis of special chromatin states favoring the creation of new genes.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…TE movements bring sequence changes to open chromatin regions, which may also aid the birth of de novo genes. Abdelsamad and Pecinka (2014) reported pollen-specific activation of 216 novel retrogenes in Arabidopsis, which supports the hypothesis of special chromatin states favoring the creation of new genes.…”
Section: Discussionmentioning
confidence: 54%
“…; see Supplemental Table 5 for a complete list). Since it is known that retrogenes are upregulated in pollen (Abdelsamad and Pecinka, 2014), to rule out the possible bias caused by retrogenes, we removed 95 reported rice retrogenes (Sakai et al, 2011) and 241 reported Arabidopsis retrogenes (Abdelsamad and Pecinka, 2014) from the phylostrata rank data sets in the TAI computation.…”
Section: The Transcriptomes Of Pollen Are Evolutionarily Youngmentioning
confidence: 99%
“…This is important because genes identified in transcriptome data are not often translated into functional proteins. Some important passenger's genes are retrogenes whose mobility allows them to reach their transcriptional maximum in pollens (Abdelsamad and Pecinka, 2014). Sporadic flowering is an active process that could deplete the vital energy required for survival and hence prompt death of bamboo clumps.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previously, it was shown that small interfering RNAs originating from genome transposable elements renders the FLOWERING LOCUS C (FLC)-Ler subject to repressive chromatin modifications with implications in the natural flowering behaviour in Arabidopsis(Liu et al, 2004). These studies(Liu et al, 2004;Abdelsamad and Pecinka, 2014; Tamaki et al, 2014) highlight the importance of mobile genetic elements in flowering. A previous study on in vitro chemical induction of flowering boom in Bambusa oldhamii identified transposable elements, stress related proteins and proteins with unknown functions(Lin et al, 2010) akin to the present study.…”
mentioning
confidence: 93%
“…A few studies have demonstrated that retrogenes may also be functional in plants. Retrogenes are up-regulated and play a role in pollen development in Arabidopsis (Abdelsamad and Pecinka 2014). Rice retrogenes have persisted longer than would be expected for nonfunctional elements and are under selection (Wang et al 2006).…”
Section: Introductionmentioning
confidence: 99%